Censorship detected in UG (Uganda) - Voidly (2026)
CRITICAL severity censorship detected in Uganda. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: UG-2026-0086
Keywords: censorship; UG; censorship; critical